Perkembangan industri di indonesia: Dari sektor tradisional ke era digital - yasmin, hawa arini dina (Maliki Interdisciplinary Journal, 2025)
This article examines various industrial developments in Indonesia with a focus on the transformation of the traditional sector into the digital era. Since the beginning of independence, Indonesia’s industry has gone through various stages, ranging from relying on natural resources to transitioning to a more technology and innovation-based industry. In the context of globalization and advances in information technology, many traditional industries are adapting by utilizing digital technology to improve efficiency and competitiveness. This research uses qualitative methods to analyze the impact of these changes on the economic and social structure of the community. The results of the study show that the digitalization of industry not only increases productivity in the economy, but also creates new advantages and challenges, especially for workers who need to adapt to technological developments. In addition, education and training must be improved to ensure human resources are able to adapt and compete along with the changing times. Thus, this article is expected to contribute to stakeholders in developing policies that support sustainable and inclusive industrial development in Indonesia.